Deteksi Dini Faktor Risiko Penyakit Tidak Menular pada Lansia: Analisis Data SKILAS Kabupaten Gresik 2025 - Lilik Djuari; Raudia Faridah Humaidy; Shafira Meidyana; Nurul Yulianti; Anik Luthfiyah (Fakultas Kesehatan Masyarakat Indonesia, 2026)
Background: The increasing proportion of the elderly population in Indonesia has led to a growing burden of non-communicable diseases (NCDs) such as hypertension, diabetes mellitus, and dyslipidemia. The Elderly Health Screening Program (Skrining Kesehatan Lansia or SKILAS) is implemented in all community health centers (public primary care service) in Indonesia to enable early detection of NCD risk factors and facilitate timely interventions. Objective: This quantitative descriptive study used a cross-sectional design with secondary data from the 2025 SKILAS program obtained from the Gresik District Health Office. Variables analyzed included demographic characteristics (age, sex), blood pressure, blood glucose, total cholesterol, uric acid, body mass index (BMI), and activities of daily living (ADL) assessment. Data were analyzed descriptively using frequency and percentage distributions. Methods: This quantitative descriptive study used a cross-sectional design with secondary data from the 2025 SKILAS program obtained from the Gresik District Health Office. Variables analyzed included demographic characteristics (age, sex), blood pressure, blood glucose, total cholesterol, uric acid, body mass index (BMI), and activities of daily living (ADL) assessment. Data were analyzed descriptively using frequency and percentage distributions. Results: Among elderly participants screened at 35 community health centers in Gresik, most were aged 60-69 years and predominantly female. The proportion of elderly with blood pressure ≥140/90 mmHg was approximately 40–50%, total cholesterol >200 mg/dL around 30%, and random blood glucose ≥200 mg/dL about 10–15%. Most participants were overweight, and approximately 20% showed a decline in daily activity performance. Conclusion: The screening results indicate a high prevalence of NCD risk factors among the elderly in Gresik District. Strengthening promotive and preventive efforts through nutrition education, increased physical activity, and consistent medical follow-up at community health centers is essential to reduce the risk of chronic complications. Suggestion: Comprehensive non-communicable disease prevention should be implemented through health education, adequate risk-factor management, and continuous clinical monitoring.